The significance of music-pedagogical work of Zorislava M. Vasiljević for Music Education in Lower Elementary School Grades - Ilić, Miona (Norma, 2022)
Zorislava M. Vasiljević (1923-2009) dedicated her professional path to noticing the deficiencies, to pursuing adequate scientific conformations and solutions, as well as to finding the appropriate procedures which can be used in working on the music literacy in Serbia. On that path, her guidance was the thought of her father, Miodrag A. Vasiljević (1903-1963). She improved and complemented his idea with important segments of other methods, thus forming a unique Combined functional method. This paper concerns the life of Zorislava Vasiljević, the Combined functional method with all its characteristics in the field of melody and rhythm, together with the impact that the life’s work of Zorislava Vasiljević has had on the curriculum of Music Education in the first to fourth grades. With a desire to talk about the significance of her music-pedagogical work for Music Education in Lower Elementary School Grades, we had to consider her author’s textbook literature, done with a lot of effort, as an unavoidable segment. Among the textbooks written by Professor Zorislava Vasiljević, the special attention was given to her publication Music Primer.